ANY QUESTIONS? IDEAS FOR ENCOURAGING MORE AND BETTER STUDENT QUESTIONS - Jacobs, George M.; Renandya, Willy Ardian (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
One of the key characteristics of student-centered learning is the active involvement of students in the learning process, where they co-construct knowledge with the guidance of the teachers and their peers. The co-construction of knowledge can be greatly facilitated when students respond to teachers’ questions and when they themselves generate well-thought out questions. The purpose of this article is to discuss the role of student-generated questions in a student-centred learning environment and to offer practical strategies for language teachers to guide students in asking more and better student questions in the classroom, i.e., the kind of questions that promote deeper engagement and learning.